Analysis of the Complete Plastomes of 31 Species of Hoya Group: Insights Into Their Comparative Genomics and Phylogenetic Relationships - Odago, Wyclif Ochieng; Waswa, Emmanuel Nyongesa; Nanjala, Consolata; Mutinda, Elizabeth Syowai; Wanga, Vincent Okelo; Mkala, Elijah Mbandi; Oulo, Millicent Akinyi; Wang, Yan; Zhang, Cai-Fei; Hu, Guang-Wan; Wang, Qing-Feng (Frontiers in Plant Science, 2022)
Hoya is a genus in Apocynaceae-Asclepiadoideae, known for its showy wax flowers, making it a popular ornamental plant. However, phylogenetic relationships among most Hoya species are is not yet fully resolved. In this study, we sequenced 31 complete plastomes of Hoya group species using genome skimming data, and carried out multiple analyses to understand genome variation, to resolve the phylogenetic positions of some newly sequenced Chinese endemic species, and to estimate the divergence times within the genus. We also screened possible hotspots, trnT-trnL-trnF, psba-trnH and trnG-UCC), ndhF, ycf1, matK, rps16 and accD genes that could be used as molecular markers for DNA barcoding and species identification. Using maximum likelihood (ML) and Bayesian Inference (BI), a species phylogeny was constructed. The newly assembled chloroplast genomes showed the quasi-tripartite structure characteristic for Hoya and Dischidia with a reduced small single copy (SSC) and extremely enlarged inverted repeats (IR). The lengths ranged from 175,404 bp in H. lacunosa to 179,069 bp in H. ariadna. The large single copy (LSC) regions ranged from 80,795 bp (Hoya liangii) to 92,072 bp (Hoya_sp2_ZCF6006). The massively expanded inverted repeat regions (IRs) were relatively conserved in length, with the small single-copy region reduced to a single gene, ndhF. We identified 235 long dispersed repeats and ten highly divergent hotspots in the 31 Hoya plastomes which can be used as DNA barcodes for species identification. The phylogeny supports Clemensiella as a distinct genus. Hoya ignorata is resolved as a relative to Clade VI species. This study discloses the advantages of using chloroplast genome data to study phylogenetic relationships.